2013
DOI: 10.1155/2013/214297
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Leishmaniasis of the Eyelid: A Case Report

Abstract: Cutaneous leishmaniasis is endemic in certain areas of Iran, and in recent years, there has been an increase in the number of reports for rare and new forms of cutaneous leishmaniasis. We describe one unusual clinical form of cutaneous leishmaniasis. In a 27-year-old man, who noted a pimple on the upper eyelid 4 months before. The lesion was nodular and measured 1 cm × 1 cm in diameter. A diagnosis of eyelid cutaneous leishmaniasis was made, and treatment was started with intramuscular meglumine antimonate. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 6 publications
0
18
0
Order By: Relevance
“…Nasiri et al described a case of CL on lower lip [ 15 ]. Ayatollahi et al described a case of unusual cutaneous leishmaniasis involving a solitary lesion on the right eyelid (ocular leishmaniasis) [ 7 ]. Sadeghian et al described a case of ocular leishmaniasis on lower and upper right eyelid margins [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nasiri et al described a case of CL on lower lip [ 15 ]. Ayatollahi et al described a case of unusual cutaneous leishmaniasis involving a solitary lesion on the right eyelid (ocular leishmaniasis) [ 7 ]. Sadeghian et al described a case of ocular leishmaniasis on lower and upper right eyelid margins [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…2 It has been suggested that the frequent movements of the eyelid prevent insects from biting the skin in that region. 3 The diagnosis of cutaneous leishmaniasis is based on clinically typical lesions, history of exposure and the endemicity of the disease in the region. 1 The most commonly used diagnostic method is the presence of amastigotes (Leishman-Donovan bodies) in macrophages on the microscopic examination of the tissue smears (obtained as tissue biopsy, needle aspirates or slitskin smears) stained with Giemsa or haematoxylin and eosin stain.…”
Section: Discussionmentioning
confidence: 99%
“…Some rare manifestations of CL have been described (3)(4)(5). Here we present an interesting case of CL because of the rare location of the lesion in the palmoplantar region.…”
Section: Introductionmentioning
confidence: 86%